Implementación de una unidad didáctica para la enseñanza de la geometría a través del fútbol en estudiantes de grado séptimo del colegio distrital paulo freire (2017)
Teaching math in ways other than those framed under traditional models is a prevailing necessity in school, since students today are under the "charm" of the distractions offered by new technologies, making their interest in learning decreases and more so when it continues to perform as it did some decades ago. T